Specificity in strength training: A review for the coach and athlete - Sale, D.; MacDougall, D. (Canadian Journal of Applied Sport Sciences, 1981)
Two theories were evaluated in light of the published literature. 1. Strength training exercises should simulate the sport movement as closely as possible in terms of movement pattern, movement velocity, type of contraction, and force of contraction. 2. It is only necessary to train muscle groups. Increases in strength can be re-educated into a sports action. - Movement Pattern - Contraction Velocity - Type of Contraction - Contraction Force SUMMARY AND IMPLICATIONS 1. Strength training should be as specific as possible. The movement pattern and contraction speed, type, and force should replicate the intended activity. Any departure from one of these factors will result in inappropriate adaptations. 2. High-velocity sports may need supplemental low-velocity training to induce maximal adaptation within the muscles. 3. Supplementary maximal training may be beneficial because it stimulates maximal adaptation. However, that adaptation should be achieved before serious technique work begins. 4. Non-specific training has a high probability of being counter-productive. 5. There is no evidence to support the "re-education of strength gains" hypothesis.